Annealing Effect on Structural and Optical Properties of 〖Cd〗_(0.91) 〖Ni〗_(0.09)o Thin Films Prepared by Chemical Spray Pyrolysis - Haneen F. Abd; Ziad T. Khodair (ASJ - Academic Science Journal, 2024)
In this study, CdO:Ni thin films with 300 nm thickness and 9% nickel concentration were prepared by spray pyrolysis on glass substrates and annealed at different temperatures (350, 400 and 450) °C. The prepared films were characterized using X-ray diffraction (XRD), Field Emission Scanning Electron Microscopy (FE-SEM), and UV visible spectroscopy measurements in the wavelength (400-900) nm. XRD analysis exhibited a cubic crystalline structure. The crystalline size increased with the increase of temperature (23, 61,104,88) nm, also. The prepared annealed thin films showed high optical transmittance in the visible region The optical band gap energy (Eg) be found (2.51, 2.40, 2.27, and 2.22,) eV in before and after annealing temperature (350°C, 400°C and 450°C) respectively.